The Impact of Vertical Plasma Motion on the Evolution of Predawn Equatorial Plasma Bubbles on the Dayside - Hyosub Kil; Joseph D. Huba; Larry J. Paxton (Geophysical Research Letters, 2024)
Abstract This study investigates the impact of vertical ionospheric drift during daytime on the evolution of predawn equatorial plasma bubbles by conducting model simulations using “Sami3 is Another Model of the Ionosphere.” The upward drift of the ionosphere transports bubbles to higher altitudes, where their lifetime is set by the atomic oxygen photoionization rate. While the bubbles generated at predawn persist into dayside, the bubbles generated shortly after sunset diminish before sunrise. Therefore, post‐sunset bubbles do not contribute to daytime electron density irregularities. Bubbles maintain their field‐aligned characteristics throughout the daytime regardless of the vertical ionospheric drift. This property allows bubbles to exist near the magnetic equator despite poleward plasma transport by the fountain process. The shift of irregularity concentration to higher latitudes over time in satellite observations is explained by the combined effect of transport of bubbles to higher altitudes and rapid refilling of depletions near the magnetic equator.